EFFECT OF CULTURE CONDITIONS ON RECOMBINANT GFP PRODUCTION BY ARABIDOPSIS THALIANA (L.) HEYNH. HAIRY ROOTS - Thi Phuong Nga Mai (Tạp chí Khoa học Đại học Đà Lạt)
Recombinant proteins are produced by various expression systems. In the present study, the production and stability of green fluorescent protein (GFP) produced by Arabidopsis thaliana hairy roots were investigated. The parameters included the culture media and shaking speeds. The results showed that the B5 medium supplemented with 3% sucrose was the best among the three studied media for hairy root growth and GFP production, as the hairy roots exhibited a preference for nitrate over ammonium salt as a nitrogen source. GFP production increased from two to four weeks of culturing in the B5 medium, in which hairy root line 30 reached approximately 27 mg/L GFP after four weeks. The lower shaking speed of 60 rpm was better for GFP production and for the stability of the His-tag attached to GFP. These results provide new insights into recombinant protein production by the hairy roots of Arabidopsis thaliana. This will pave the way for better optimization of recombinant protein production using plant cell systems, which could reduce the immunological response when these recombinant proteins are produced and used for therapeutic applications in animals or humans.